Perinatal outcomes of pregnancies with borderline versus normal amniotic fluid index: A prospective study - Mishra, Anamika; Neupane, Ram Prasad; Prasad, Pratap Narayan; Thakur, Abhishek Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Amniotic fluid cavity filled with liquor amnii is a natural floating bed for fetus required  for its existence and growth in sterile environment, regulation of temperature, avoidance of external injury and reduction of impact of uterine contractions. Amniotic fluid has high influence on the fetal outcome and is directly related to the perinatal morbidity and mortality. This study aims to compare the pregnancy outcomes in patients with borderline AFI between 5-8 cm and normal AFI >/= 8-24 cm.Method: This was a prospective observational study of 108 pregnant women. After Amniotic Fluid Index (AFI) assessment, they were categorized into two groups: those with AFI 5-8 cm (Group 1) and with AFI >/=8-24 cm (Group 2) accordingly. Pregnancy outcomes was noted in terms of mode of delivery, amniotic fluid colour & fetal birth weight.Result: Six(11.1%) had instrumental delivery & 28 (51.8%) had Cesarean section in borderline AFI group. 6 (11.1%) had instrumental delivery & 14 (26%) had Cesarean section in normal AFI  group. 28 (51.9%) had meconium stained amniotic fluid in borderline AFI group & 13 (24.1 %) had meconium stained amniotic fluid in normal AFI group. 110 (18.5%) newborns had fetal birth weight of